Review of current intracranial aneurysm flow diversion technology and clinical use. (25th September 2020) - Dandapat, Sudeepta; Mendez-Ruiz, Alan; Martínez-Galdámez, Mario; Macho, Juan; Derakhshani, Shahram; Foa Torres, Gustavo; Pereira, Vitor M; Arat, Anil; Wakhloo, Ajay K; Ortega-Gutierrez, Santiago
Abstract : Endovascular treatment of intracranial aneurysms (IAs) has evolved considerably over the past decades. The technological advances have been driven by the experience that coils fail to completely exclude all IAs from the blood circulation, the need to treat the diseased parent vessel segment leading to the aneurysm formation, and expansion of endovascular therapy to treat more complex IAs. Stents were initially developed to support the placement of coils inside wide neck aneurysms. However, early work on stent-like tubular braided structure led to a more sophisticated construct that then later was coined as a flow diverter (FD) and found its way into clinical application. Although FDs were initially used to treat wide-neck large and giant internal carotid artery aneurysms only amenable to surgical trap with or without a bypass or endovascular vessel sacrifice, its use in other types of IAs and cerebrovascular pathology promptly followed. Lately, we have witnessed an explosion in the application of FDs and subsequently their modifications leading to their ubiquitous use in endovascular therapy. In this review we aim to compile the available FD technology, evaluate the devices' peculiarities from the authors' perspective, and analyze the current literature to support initial and expanded indications, recognizing that this may be outdated soon.